Case report: Sustained complete remission with ivosidenib in a patient with relapsed, IDH1-mutated acute leukemia - Sahasrabudhe, Kieran; Zhao, Weiqiang; Berg, Miriam; Bhatnagar, Bhavana (Frontiers in Hematology, 2023)
Older patients with acute lymphoblastic leukemia (ALL) have a poor prognosis with a 5 year overall survival rate of only 10-20%. This is attributable to patient comorbidities, poor performance status, and high risk disease biology. The prognosis for patients with relapsed/refractory (R/R) disease also remains poor, particularly for patients who are not candidates for CD19 or CD22 directed therapies. Additional treatment options are needed for these patient populations. The patient presented here is a 76 year old man diagnosed with precursor B-cell ALL with aberrant expression of myeloid markers and lacking significant CD19 or CD22 expression. A three year remission was achieved with one cycle of CVP (cyclophosphamide, vincristine, prednisone) followed by 22 months of maintenance DOMP (dexamethasone, vincristine, methotrexate, 6- mercaptopurine) prior to relapse. He was then treated with one cycle of salvage CVP which was complicated by a stroke resulting in hemiparesis. Next generation sequencing (NGS) was performed on the relapsed bone marrow which revealed the presence of an R132H mutation in the Isocitrate Dehydrogenase 1 (IDH1) gene. He was subsequently treated with the IDH1 inhibitor ivosidenib and remained in a second remission for nearly one year. IDH1 mutations are present in up to 14% of acute myeloid leukemia (AML) cases and are seen more rarely in ALL, particularly in cases involving aberrant expression of myeloid markers. Ivosidenib has demonstrated efficacy in patients with IDH1-mutated AML but has not been extensively studied in other hematologic malignancies. This case demonstrates the role of NGS in revealing treatment options in patients with otherwise limited therapies.